Life tables of Greek population by marital status: 1989-1993 - Κοτσυφάκης Γεώργιος; Τσίμπος Κλέων (The Greek Review of Social Research, 1997)
Life tables by marital status for the Greek population are constructed using census data (1991) and vital statistics (1989-1993). It was found that among the four marital categories, never married men and women experience the lowest life expectancy at birth followed by widows, divorced and married people. Differentials in expectation of life at any age between the four marital groups are more pronounced among men but they are diminishing with age. Differences in personal practices and babbits between married and non married people as well as family support roles can partly explain the observed mortality differentials by marital status.